2020
DOI: 10.21203/rs.3.rs-34039/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictors of Malnutrition among Pregnant Women in Ethiopia: Systematic Review and Meta-Analysis

Abstract: Background Women of reproductive age are especially vulnerable to protein energy deficiency and under nutrition. Malnutrition is the underlying cause of significant maternal morbidity and mortality. In addition, malnutrition among women is a major risk factor for adverse birth outcomes. Its extent and consequences is highly prevalent in developing countries. This major burden can be reduced through effective nutritional interventions. So, up to date meager evidences were warranted. Therefore, this systematic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…Several community-based studies were done in Ethiopia regarding undernutrition in pregnant women. 28 42 The average pooled prevalence of undernutrition from these studies was 29.07%, 43 where the lowest (14.4%) and highest (47.2%) prevalence were reported from Amhara and Oromia regions, respectively. 28 , 36 In addition, these studies identified factors associated with undernutrition in women of reproductive age including age, marital status, level of education, income, workload, women’s decision, dietary advice, dietary diversity, meal frequency, family planning, unplanned pregnancy, antenatal care follow-up, parity, gravidity, gestational age, and iron supplementation.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several community-based studies were done in Ethiopia regarding undernutrition in pregnant women. 28 42 The average pooled prevalence of undernutrition from these studies was 29.07%, 43 where the lowest (14.4%) and highest (47.2%) prevalence were reported from Amhara and Oromia regions, respectively. 28 , 36 In addition, these studies identified factors associated with undernutrition in women of reproductive age including age, marital status, level of education, income, workload, women’s decision, dietary advice, dietary diversity, meal frequency, family planning, unplanned pregnancy, antenatal care follow-up, parity, gravidity, gestational age, and iron supplementation.…”
Section: Introductionmentioning
confidence: 82%
“… 28 , 36 In addition, these studies identified factors associated with undernutrition in women of reproductive age including age, marital status, level of education, income, workload, women’s decision, dietary advice, dietary diversity, meal frequency, family planning, unplanned pregnancy, antenatal care follow-up, parity, gravidity, gestational age, and iron supplementation. 30 , 32 35 , 43 …”
Section: Introductionmentioning
confidence: 99%
“…The higher prevalence of abortion in this study is in line with studies conducted in Ghana, Mozambique, and Ethiopia [ 13 , 34 – 36 ]. The higher burden of abortion in East Africa could be explained by inadequate coverage and access to family planning services, higher magnitudes of unwanted pregnancy, and higher burdens of acute and chronic malnutrition among reproductive-aged women [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%